O8.7. STIMULATING THE BRAIN TO IMPROVE INTROSPECTIVE ACCURACY IN SCHIZOPHRENIA. (9th April 2019) - Pinkham, Amy; Bass, Emily; Klein, Hans; Vanneste, Sven
Abstract: Background: Introspective accuracy (IA) refers to the ability to accurately assess one's own skills and capabilities. Recent work provides evidence that IA deficits in schizophrenia that are predictive of everyday functioning and has demonstrated reduced activation for patients in right rostrolateral prefrontal cortex (rlPFC), a region thought to be critical for successful IA. Together, these findings suggest that increasing activity of the rlPFC in individuals with schizophrenia may result in improved IA, which may then lead to better functional outcomes. The current study aimed to directly test this hypothesis by using transcranial Direct Current Stimulation (tDCS) to increase activity in the rlPFC in individuals with a diagnosis of schizophrenia or schizoaffective disorder. Methods: Thirty-five participants completed two brain stimulation sessions (one active and one sham) approximately one week apart. Active stimulation occurred at 1.5mA for 20 minutes. The sham condition included 5 seconds of stimulation at 1.5mA that was then discontinued for the remainder of the session. In both conditions, the anode was placed immediately over the right rlPFC, with the cathode placed on the left bicep. After each session, participants performed neurocognitive (i.e. Wisconsin Card Sorting Task; WCST) and social cognitive (i.e. emotion recognition; ER40) tasks that were modified to allow for assessments of IA. Participants also completed a novel emotion recognition task that utilizes a signal detection framework to allow for measurement of IA while controlling for task difficulty. Results: Paired samples t-tests indicated that overall task accuracy on both the WCST and ER40 did not differ across stimulation conditions (ps>.77). IA was calculated for the WCST and ER40 tasks by obtaining a type 2 ROC (receiver operating characteristic) curve and computing the area under this curve (AUROC2). Paired samples t-tests failed to reveal any improvement in IA during active stimulation as compared to the sham condition for either ER40 (active mean: 0.57; sham mean: .53; t(34)=.76, p=.46) or WCST (active mean: 0.56; sham mean: .53; t(34)=.01, p=.99). Data analyses for the novel emotion recognition task are underway. Discussion: These preliminary findings indicate that stimulation of right rlPFC via tDCS does not improve introspective accuracy abilities in patients with schizophrenia spectrum illnesses. It is possible that greater durations of stimulation or repeated stimulation sessions are required to promote behavioral change. However, given the strong links between rlPFC and IA, continued attempts to increase neural activation with these regions seems warranted.